2017
DOI: 10.1016/j.ygcen.2016.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Public exposure and number of conspecifics have no influence on ovarian and adrenal activity in the cheetah (Acinonyx jubatus)

Abstract: Cheetahs in managed zoological collections do not reproduce efficiently, a problem that may be related to environmental/management stressors. In this study, we examined 17 adult female cheetahs to determine the influence of two environmental factors, (1) being housed on- or off-exhibit and (2) number of adult conspecifics (males and/or females) in nearby enclosures, on profiles and concentrations of ovarian and adrenal hormones. Secondarily, we assessed a subset of group-housed siblings (n=5 females in groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 52 publications
1
14
0
Order By: Relevance
“…The reproductive activity of male cheetahs also appears to be higher when they are held off‐exhibit than when they are on‐exhibit (Koester et al. , ). Given that much of the research available on the reproductive biology of felids has been conducted in captivity, it is tempting to speculate that differing enclosure conditions may have contributed to the variability in oestrous cycles and ejaculate traits of the different species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reproductive activity of male cheetahs also appears to be higher when they are held off‐exhibit than when they are on‐exhibit (Koester et al. , ). Given that much of the research available on the reproductive biology of felids has been conducted in captivity, it is tempting to speculate that differing enclosure conditions may have contributed to the variability in oestrous cycles and ejaculate traits of the different species.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals selected for breeding should also be kept off‐exhibit and have their exposure to humans minimised (Koester et al. , ).…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, our laboratory has focused on feces as a resource for non-invasively understanding reproductive mechanisms and determining reproductive status, especially via hormone metabolite monitoring. For example, the evaluation of serially collected fecal samples from the cheetah has been useful for characterizing this species’ unique reproductive cycle [ 4 , 24 , 25 ], exploring the influence of exogenous gonadotropins [ 26 ], including for timed artificial insemination [ 8 ], and for examining the influence of management factors on reproductive success of both females [ 27 , 28 ] and males [ 29 , 30 ]. Particularly important is that fecal samples can be collected frequently from a cheetah’s enclosure without causing perceived stress or altering best practice animal care.…”
Section: Introductionmentioning
confidence: 99%
“…The authors concluded that their findings indicated a psychological attachment may exist between members of a coalition (Ruiz‐Miranda et al, ). An additional study by Koester in 2017 revealed males housed in coalitions had higher ejaculation quality, and higher concentrations of androgen, further suggesting the benefit of housing males in coalition settings not only for efficiency but for economic purposes (Koester, Freeman, et al, ).…”
Section: Discussionmentioning
confidence: 99%